THE COMMERCIALIZATION OF HIGHER EDUCATION: TRENDS, IMPACTS, AND FUTURE CHALLENGES - Fadly Alan Nur Datumula (Jurnal Ilmu Pendidikan dan Budaya, 2025)
This study maps the global research landscape concerning higher education commercialization. Driven by economic globalization and reduced public funding, universities have progressively transitioned from societal public goods to competitive commercial services. Despite extensive qualitative evaluations on this institutional shift, the domain's intellectual architecture remains fragmented. To bridge this analytical gap, a hybrid methodology was executed, integrating a Systematic Literature Review (SLR) via the PRISMA protocol and bibliometric mapping using VOSviewer. Based on 136 core Scopus articles (1985–2024), the historical trajectory is classified into three evolutionary phases: Initiation (1985–2002), Acceleration (2003–2014), and Maturation (2015–2024). Actor mapping identifies Wu, W. as the most productive author, the University of Tehran and Moscow Aviation Institute as leading institutions, and the United States and United Kingdom as the dominant contributing nations. Spatial network analysis highlights a dense, collaborative UK-European axis, while the US acts as a macro-structural bridge to Eastern research hubs. Keyword co-occurrence clustering reveals "higher education" (n = 72) and "commercialization" (n = 54) as central nodes with strong structural proximity to technology transfer and innovation networks. The synthesis reveals that future governance must navigate critical challenges regarding marketization pressures, technology transfer regulation, and socio-economic access barriers. Ultimately, this research outlines emerging thematic directions toward institutional entrepreneurship, administrative decentralization, and tripartite co-regulatory research and development (R&D) alliances, offering strategic structural insights for policymakers balancing commercial pragmatism with public good values.